Estudo de reações fisiológicas de novilhas de três graus de sangue, nas condições de Viçosa, Minas Gerais. I-temperatura retal e ritmo respiratório - Gonçalves de Assis, Airdem; Milagres , João Camilo; Américo Garcia, José; Carneiro , Luiz Hemetério D M; Ribeiro Gomes, Fábio (Revista Ceres, 2025)
The study was conducted at the Federal University of Viçosa in the Zona da Mata, Minas Gerais State from September 16, to January 19, 1971, covering spring time and part of the summer.